A novel variant in the SLC4A3 gene with high penetrance in a family with short QT Syndrome. (24th May 2021) - Kovacs, B; Graf, U; Magyar, I; Baehr, L; Maspoli, A; Duru, F; Berger, W; Saguner, AM
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Short QT syndrome (SQTS) is a rare, autosomal dominant disease causing sudden cardiac death (SCD). Current guidelines recommend genetic testing. Associated variants in KCNQ1, KCNH2, KCNJ2 and SLC4A3 genes have been reported. Purpose: We report a family with a variant in the SLC4A3 gene with several presentations of SCD and high clinical penetrance of SQTS. Methods: We performed a post-mortem genetic testing in the index patient in whom prior ECG was available. Subsequently, clinical and electrophysiological work-up and cascade screening (CS) of the detected suspected variant was carried out in available relatives. Results: The index patient had suffered a SCD at the age of 17 (figure, upper panel, arrow). A previously registered ECG showed a shortened QTc of 340ms (figure, lower panel). Autopsy revealed no structural heart disease. Post-mortem genetic testing revealed variants in the LDB3, MYH7 and a novel heterozygous missense variant, p.(Ser1039Arg) also in the SLC4A3 gene. Although predictive bioinformatic algorithms (AlignGVGD, SIFT, MutationTaster, Polyphen2) showed conflicting classifications, family history was notable for SCD without post-mortem genetic work-up in three second degree relatives (figure, upper panel, patients 207, 208 and 305, age of death 33, 25 and 33 years respectively). CS was performed in first and second degree relatives of the index patient and was highly suggestive for disease association of the variant in the SLC4A3 gene with co-segregation in all clinically affected family members. Only one patient with the variant had a normal QTc (figure, upper panel, patient 202) of 407ms, however this patient was on regular QT-prolonging medication (risperidone and loperamide). Conclusion: Genetic testing revealed a novel in the SLC4A3 gene, which was recently implicated in the pathogenesis of the SQTS. Although predictive bioinformatic algorithms yielded conflicting results, CS of family members suggests a likely pathogenicity (class IV) of the variant. Further CS or functional tests are necessary to establish causality.